Neural structures of two freshwater fishes, Notopterus notopterus (Notopteridae)[knife-fish; belida] and Hampala macrolepidota (Cyprinidae) - Adli, D.S.H.; Ismail, M.Z.; Saat, R. (1994)
The central nervous systems of two species of freshwater fish, Hampala macrolepidota and Notopterus notopterus were examined. Specifically, the neural structures involved in visual input processing of both fishes are compared. The findings are in turn correlated to the feeding behaviour and the ability of the fishes to live successfully in each own habitat